Developing Interprofessional Clinical Rotations in Low Income Areas: Learned Strategies for Healthcare Educators. (26th June 2020) - Stidham, April L.
Abstract: This chapter describes the setting for interprofessional education and practice with an emphasis on the development of interprofessional clinical rotations. The barriers and challenges for healthcare facilities serving patients in rural areas with limited resources is outlined. The process for establishing academic and healthcare institutional partnerships is also discussed, along with strategies to prepare faculty to serve as preceptors.